Pelatihan Digital Marketing Kewirausahaan dan Pendampingan Halal Minumam Carica NSR Desa Bawang Kabupaten Batang - Khasanah, Dian Ratu Ayu Uswatun; Muzammil, Moh; Masduki, Lusi Rachmiazasi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
During the post-Covid-19 pandemic, MSMEs began to be reluctant to get back up, after being in suspended animation during the pandemic. As is the case with community service partners who have a typical Carica beverage entrepreneur with the NSR brand located in Bawang village, Batang district, Central Java. The 3 years of non-production has caused several partner problems, including the end of PIRT legality and upgrading of HALAL certification, equipment that is no longer suitable for use because it has not been in production for a long time, and also conventional marketing problems. This third thing made the team consisting of lecturers and students carry out community service through mentoring and training methods for Carica's NSR MSME partners. With the provision of equipment assistance, assistance in HALAL management, and digital marketing training, it provides benefits for partners. After the dedication drink activity was held, the public or consumers are increasingly consuming carica with the NSR brand because in November 2022 a HALAL certificate has been issued. Then the partners have a virtual shop to market NSR Carica drinks on social media Tiktok Shop and e-commerce Shopee. With a combination of conventional marketing and digital-based marketing, the results of increasing sales and increasing number of employees are obtained.